The Development of the Ear of Rabbit Embryo - Roongruangchai, Jantima; Pilakasiri, Kajee; Sangjan, Noppadon; Phongchapo, Mana; Koedpuech, Kasem; Amonmattajit, Nutchaya (Siriraj Medical Journal, 2004)
The ear consists of three parts which are different origin but function as one unit. The internal ear originates from the surface ectoderm covering the lateral sides of myelencephalon at the fourth week. This ectoderm thickens to from the otic placode and then invaginates to form the otocyst and splits from the surface ectoderm. The otocyst or otic vesicle divides into 2 parts, the ventral cochlear and the dorsal utricular portions. The cochlear gives rise to the saccule and the cochlear duct while the utricular portions gives rise to the uteicle, semicircular ducts and endolymphatic duct. These epithelial structures so formed are known as the membranous labyrinth. The bony labyrinth and the perilymphatic space originate from the mesenchy otic capsule. The middle ear, consisting of the tympanic cavity and the auditory tube, are lined with epithelium of the endodermal origin of the first pharyngeal pouch. The ear ossicles, the malleus and incus are derived from the first and the stapes from the second arch cartilages. The external auditory meatus develops from the first pharyngeal cleft, while the tympanic membrane originates from the mesenchyme between. In order to understand ear development, pig and chick embryos were used in the laboratory studies. Since the pig embryos are presently not available, this compared the ear development of the pig and rabbit embryos, which indicate that the ear of the pig and rabbit develob in the same manner and the rabbit embryos can be used in the future instead of pig embryos for studying ear development.